Pengembangan Sistem Informasi Sertifikasi Menggunakan Metode Agile - Septiani, Lintang; Ramdani, Dewi; maula, Anjas Teguh; Nugroho, Nur Budi; Ar Ridho, Muhammad Fikri (Digital Transformation Technology, 2024)
The Academy Support Unit (UPA) at Indramayu State Polytechnic has an important role in organizing certification services to measure the skills, knowledge, and work attitudes of graduates according to industry standards. This competency certification is designed to improve the competitiveness of graduates, so that they are more easily accepted in the workforce. However, the certification process still faces several challenges, especially in administration which tends to be prone to recording errors. So that the process of reporting results is also constrained. To overcome these obstacles, Indramayu State Polytechnic developed a website-based application with the Laravel Framework called the Training and Competency Test Service Information System. This study uses an agile method approach. It is expected that the entire administrative process, from registration to reporting results, can improve efficiency and transparency. This step is also expected to support the vision of vocational education in producing competent graduates who are ready to compete in the global job market.